O perfil da inovação em serviços no Brasil: uma comparação internacional - Kinoshita, Karoline Ferreira (2013)
The service sector has represented the largest share of Gross Domestic Product (GDP) both developed countries, representing over 70% of GDP, as emerging countries , as in the case of Brazil in which represented about 68% of GDP in 2009. Thus, innovation in the industry has achieved critical importance for obtaining competitive advantages by national companies and also for the opening of the economy and the country's participation in global markets. However, there is little amount of work with a broader national approach to innovation in the sector. The objective of this work is then to identify and analyze the characteristics of the innovative performance of Brazilian companies to provide services in Brazil in the period 2006-2008, through a descriptive and comparative analysis from the Technological Innovation Survey (Pintec 2008) of the Instituto Brasileiro de Geografia e Estatística (IBGE) and the Community Innovation Survey (CIS 2008) Statistical Office of the European Union (Eurostat). It was found that innovation in services in Brazil is characterized by the realization of low investments in generation and accumulation of knowledge, originating mainly from the activities of Research and Development (R&D); for innovative activities, outlays and cooperating partners aimed at obtaining external knowledge for further adaptation and use within companies, revealing the nature of incremental innovations and reactive attitude of service organizations; the low government incentives, which do not offer technical and economic resources to innovate more aggressively and the macroeconomic problems encountered; the organizational innovations over the marketing innovations, due to the need to improve production techniques, which are essential to increased productivity and cost reduction; the use of tags that reduce the uncertainty in time for the customer to choose a service; and concern about the lack of skilled labor, caused the migration of jobs in the industrial sector due to the various factors that boosted the services sector, such as the increased use of technology. These characteristics indicate the use of a defensive strategy by the Brazilian companies that need additional investment to the country to be closer to selected European countries, which have invested heavily in R&D and adopt a culture focused on innovation.